The role of food price inflation in Lesotho. (27th February 2013) - Thamae, Retselisitsoe I.
The paper analyses the role of food price movements in inflation within the Lesotho's economy. The results reveal that food inflation has generally not only been more volatile and higher than non-food inflation, but also more persistent than the inflation of non-food products. Furthermore, food price movements are discovered to have significant impact on core inflation, thereby giving evidence that food prices contain some useful information about the underlying inflation trends in Lesotho. On the other hand, the results have shown the presence of strong second-round price effects between food and non-food inflation. These findings, therefore, imply that the setting and communication of monetary policy in Lesotho should be based on developments in underlying inflation rather than overall inflation. However, any attempt to capture the underlying inflation using measures that exclude food items only on the basis of their high volatility would be unjustified.